Dental Care During Pregnancy A Narrative Review - Gupta, Ankita; Agrawal, Rashmi (Journal of Orofacial Research, 2025)
Pregnancy brings about substantial hormonal and physiological shifts that can affect oral health, making women more vulnerable to conditions like gingivitis, pyogenic granuloma, and oral candidiasis. If these oral lesions are not addressed, they can compromise both the mother’s comfort and the baby’s health. This review explores the relationship between pregnancy and oral health, with a focus on the frequency, clinical features, and management of oral lesions during pregnancy. It underscores the value of maintaining proper oral hygiene, attending routine dental appointments, and seeking prompt care for any dental concerns. The review also affirms that both preventive and restorative dental treatments are safe and important throughout pregnancy. Educating expectant mothers about oral health is crucial, as it enables early detection and prevention of oral diseases. Ultimately, proactive oral care during pregnancy leads to improved health outcomes for both mother and child.